Recent developments of biomaterial scaffolds and regenerative approaches for craniomaxillofacial bone tissue engineering - Gundu S.; Varshney N.; Sahi A.K.; Mahto S.K. (My University, 2025)
Bone defects in the craniomaxillofacial (CMF) region occur as a result of trauma, cancer excisions, congenital defects and deformities. CMF bone reconstruction is challenging due to anatomical complexity, functionality and aesthetic conditions. Bone grafting is the current standard approach to reconstruct CMF injuries. However, it possesses certain limitations to restore the structural and functional defects of CMF bone. To overcome these limitations, tissue engineering and regenerative methodologies have been developed to reconstruct damaged bone tissues. Various biomaterial scaffolds made up of synthetic, natural and ceramics materials have been used to repair craniofacial bone tissues. In this review, we have first discussed the structure of CMF bone, bone tissue engineering and mechanical properties required for CMF bone tissue engineering. Subsequently, a detailed survey on the recent research innovations of tissue engineering with various types of biomaterial scaffolds, stem-cell sources, growth factors and functional scaffold fabrication techniques to repair and remodel the CMF defects has been presented. © 2022, The Polymer Society, Taipei.